A região cultural como categoria de análise da materialização da cultura no espaço Gaúcho - Neto, Helena Brum [UNESP] (2009)
The regional matter, at the present time, presents different analysis perspectives which can be evidenced by the transformations imposed by the globalization process in the space organization. In this perspective, this paper intends to consider the area under the optics of culture, considering it as a true promoter agent of the space cuttings, once they are constituted in one of the structural pillars that obstruct the homogenization of the cultural codes, taking the responsibility for the diversity in ways of organization of the space. The concept of region is focused through symbolic processes inherent to culture, which materializes, in the space, its characteristic forms, originating regional cuttings with cultural connotation, in other words, the cultural areas. To exemplify such reflections, the regional context of Rio Grande do Sul is approached, in which, the regionalism becomes evident by the construction of the gaúcho as a representative regional type of the unit in the diversity.